What drives SME investment in digitalisation? Micro-data evidence for Ireland - Janez Kren; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2024)
In this paper, we use novel firm-level microdata for Ireland to explore the factors that determine the investment in digitalisation for micro, small and medium-sized enterprises (SMEs). More specifically, we use cross-sectional survey data to explore whether firm fundamentals or constraints act to impact digitalisation. Furthermore, we explore whether the factors determining digital investment differ from those that impact other capital expenditures (tangible fixed assets and intangibles) using both a logit and tobit approach to deal with the censoring of the investment variable and to model separately the propensity to invest and the level of investment. We also explore heterogenous effects across age, size and sector. We find that typical indicators of firm performance such as the marginal profitability of capital and overall firm profitability are strong explanatory variables for investment in digital assets. We do not find any major impact of credit market factors such as access to finance or indebtedness but interest rates have a negative effect. We find considerable variation across size, sector and age with micro and older firms much less likely to invest in digital assets.
Keywords: 330; Digitalisierung; Investitionsentscheidung; KMU; Logit-Modell; Tobit-Modell; Irland